International labour legislation in the light of economic theory - Feis, Herbert (1996)
This article is written to examine a set of closely connected questions: (1) whether this difference of doctrine between widely accepted economic theory and the effort to regulate labour conditions by international action is a real or only superficial difference; (2) to explain how such difference as may bea real has arisen; (3) to examine in the light of both sets of doctrines the possible economic gains and losses which may result from such action; (4) to indicate the problem by which countries processing different conditions of labour are faced by projects of international labour regulation, and the benefits and losses they must calculate; and (5) to analyze briefly the efforts of the International Labour Organization to take into account the possible losses and difficulties that might arise from its action, and still to carry out its main purposes.
Photocopy.
Keywords: Labor policy; Labor laws and legislation, International